Self‐Assembling Glycopeptide Conjugate as a Versatile Platform for Mimicking Complex Polysaccharides. Issue 16 (2nd July 2020) - Wang, Hanxuan; Liu, Zhichao; An, Chuanjing; Li, Haoting; Hu, Fanlei; Dong, Suwei
Abstract: Polysaccharides are a class of carbohydrates that play pivotal roles in living systems such as being chemical messengers in many vital biological pathways. However, the complexity and heterogeneity of these natural structures have posed daunting challenges on their production, characterization, evaluation, and applications. While there have been various types of synthetic skeletons that could mimic some biological aspects of polysaccharides, a safer and more easily accessed system is still desired to avoid the unnatural components and difficulties in modifying the structures. In this work, conveniently accessible self‐assembling glycopeptide conjugates are developed, where the natural O‐glycosidic linkages and phosphoryl modifications assist the self‐assembly and concurrently reduce the risk of toxicity. The generated nanoparticles in aqueous solution offer a multivalent display of structurally controllable carbohydrates as mimics of polysaccharides, among which a mannosylated version exhibits immunostimulatory effects in both cellular assays and vaccination of mice. The obtained results demonstrate the potential of this glycopeptide conjugate‐derived platform in exploiting the intriguing properties of carbohydrates in a more structurally maneuverable fashion. Abstract : A glycopeptide‐based self‐assembly containing monosaccharides and phosphates is established to display simple carbohydrates in a multivalent format, mimicking natural complex polysaccharides. Among several evaluated glycoforms, the self‐assembled mannosylated nanoparticles exhibit immunostimulatory effects both in vitro and in vivo.